2018
DOI: 10.3389/fmicb.2018.01784
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Resequencing and Pan-Transcriptome Reconstruction Highlight the Impact of Genomic Structural Variation on Secondary Metabolite Gene Clusters in the Grapevine Esca Pathogen Phaeoacremonium minimum

Abstract: The Ascomycete fungus Phaeoacremonium minimum is one of the primary causal agents of Esca, a widespread and damaging grapevine trunk disease. Variation in virulence among Pm. minimum isolates has been reported, but the underlying genetic basis of the phenotypic variability remains unknown. The goal of this study was to characterize intraspecific genetic diversity and explore its potential impact on virulence functions associated with secondary metabolism, cellular transport, and cell wall decomposition. We gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 130 publications
(166 reference statements)
3
27
0
Order By: Relevance
“…Interestingly, differences in virulence of P. minimum and P. chlamydospora isolates were reported by several authors (Santos et al ., ; Massonnet et al ., ). Massonnet et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Interestingly, differences in virulence of P. minimum and P. chlamydospora isolates were reported by several authors (Santos et al ., ; Massonnet et al ., ). Massonnet et al .…”
Section: Resultsmentioning
confidence: 97%
“…Massonnet et al . (), analysed the genomic structure (linked to secondary metabolism clusters) of distinct P. minimum isolates which displayed different virulence level, linking their pathogenic behaviour to those genomic differences. Noteworthy, no data about the virological state of such isolates were taken into account, leading to an incomplete analysis of the possible causes influencing their virulence on grapevine plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungi most strongly associated with esca wood necrosis in the trunk have been identified (Larignon and Dubos, 1997;Mugnai et al, 1999;Fischer 2006;White et al, 2011;Bruez et al, 2014;Morales-Cruz et al, 2018). While the disease was formerly associated with the presence of soft rot (caused by basidiomycetes such as Fomitiporia mediterranea), studies have identified two vascular pathogens, Phaeomoniella chlamydospora and Phaeoacremonium minimum, which are detected in trunk necrotic tissues of esca symptomatic vines (Feliciano et al, 2004;Massonnet et al, 2018;Morales-Cruz et al, 2018). Esca leaf symptoms are only observed on mature vines (more than 7 years old) in the field (Mondello et al, 2018) and cannot be reliably reproduced by inoculating vines with the causal fungi (Surico et al, 2006;Bruno et al, 2007), despite testing various methodologies (Reis et al, 2019).…”
mentioning
confidence: 99%
“…For the former, grape and fungal DNA were combined as follows: 90% grape with 10% E. lata isolate Napa209 [69], Phaeoa. minimum isolate 1119 [70], or Phaeom. chlamydospora isolate C42 [71]; 80% grape with 10% of each of two fungal isolates (in all three pair-wise combinations of the three isolates); and 70% grape DNA with 10% of each of the three fungal isolates.…”
Section: Methodsmentioning
confidence: 99%